Embolization and its Limits: Tips and Tricks - Ierardi, Anna M; Pesapane, Filippo; Horer, Tal; Reva, Victor; Carrafiello, Gianpaolo (Journal of Endovascular Resuscitation and Trauma Management, 2019)
Nowadays, non-operative management is the preferred strategy, when possible. During recent years, an improvement in embolic techniques and agents, make non-operative management more feasible and effective. In the present paper, current indications, technical requirements, advantages and disadvantages, and contraindications are discussed. Moreover, particular attention is given to the limits of the embolization procedure, suggesting some tips documented by data in the literature to overcome these limits. The most feared limit or complication is the risk of non-target embolization, especially when target tissues are noble organs. Skilled interventional radiologists, embedded into an adequate multidisciplinary team, have the available tricks to limit risks, complications, and failures.